Draft Seventh Five Year Plan 1985-90 & Draft Annual Plan 1985-86 Scheme-Wise Details Volume II - Planning Commission (Planning Commission, 1985)
During the previous Plan period there has been a massive expansion in the elementary education sector which resulted in achieving near 100% enrolment. However while attempting such massive expansion of educational facilities the qualitative aspects had more or less been ignored. During the VII Plan period the emphasis therefore will be to strengthen the quality side of the educational system by strengthening the schools with libraries, scientific equipments, furnitures and buildings. It is proposed to clear the entire backlog of land acquisition and building proposals as well as supply of furniture to these schools. The backlog in appointment of teachers in the elementary education sector is also proposed to be cleared. In consultation with the Central Building Research Institute and in collaboration with the District Rural Development Agency it is proposed to put up low cost school buildings constructed with the indigenous materials under either NREP or RLGP. It is also proposed for the first time to take up the task of covering drop outs in the age group of 11-14 through a network of non formal centres under the scheme of Univers allsation of Elementary Education.
Scheme-Wise Details
Government of Pondicherry